2010
DOI: 10.1186/1471-2350-11-1
|View full text |Cite
|
Sign up to set email alerts
|

No association of the polymorphisms of the frizzled-related protein gene with peak bone mineral density in Chinese nuclear families

Abstract: BackgroundThe Wnt/beta-catenin signaling pathway plays an important role in skeletal development. Polymorphisms of frizzled-related protein (FRZB), an antagonist of this pathway, may generate variations in bone mineral density (BMD). In this study, we analyzed the association between FRZB genotypes and peak BMD variation in the spines and hips of two relatively large samples of Chinese female-offspring and male-offspring nuclear families.MethodsWe recruited 1,260 subjects from 401 female-offspring nuclear fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 42 publications
1
28
3
Order By: Relevance
“…On the other hand, Lories et al [25] demonstrated no difference in the frequency of genotypes of the sFRP3 c.970C>G polymorphism between women with low-trauma hip fracture and elderly controls in a Belgian population. Moreover, Gao et al [22] have recently reported no association of the sFRP3 polymorphisms with peak BMD in the female offspring of Chinese nuclear families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Lories et al [25] demonstrated no difference in the frequency of genotypes of the sFRP3 c.970C>G polymorphism between women with low-trauma hip fracture and elderly controls in a Belgian population. Moreover, Gao et al [22] have recently reported no association of the sFRP3 polymorphisms with peak BMD in the female offspring of Chinese nuclear families.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have investigated the relationship between bone mass and polymorphisms in these Wnt antagonist genes such as SOST, DKK1, sFRP1, sFRP3 and sFRP4 [21,22,23,24,25,26,27,28,29]. However, the results of these studies were controversial, depending on ethnicity and the type of polymorphisms or studied genes.…”
Section: Introductionmentioning
confidence: 99%
“…The recruited female offspring were healthy. The following exclusion criteria were adopted, as in our previously reported study [20][21][22], and were used to exclude individuals from this study: (1) serious residual effects from cerebral vascular disease; (2) diabetes mellitus, except for easily controlled non-insulin-dependent diabetes mellitus; (3) chronic renal disease; (4) serious chronic liver disease or alcoholism; (5) significant chronic lung disease; (6) corticosteroid therapy at pharmacological levels for >6 months; (7) treatment with anticonvulsant therapy for >6 months; (8) evidence of other metabolic or inherited bone diseases, such as hyper-or hypoparathyroidism, Paget's disease of the bone, osteomalacia, osteogenesis imperfecta; (9) rheumatoid arthritis or collagen disease; (10) recent major gastrointestinal disease within the past year such as peptic ulcers, malabsorption, chronic ulcerative colitis, regional enteritis, or any significant chronic diarrheal state; (11) significant disease in any endocrine organ that would affect bone mass; (12) hyperthyroidism; and (13) any neurological or musculoskeletal condition that could be a nongenetic cause of low bone mass.…”
Section: Subjectsmentioning
confidence: 99%
“…In vitro studies of human alveolar macrophages have shown that oxidative stress caused by acute cigarette smoke extract (CSE) exposure increases the release of interleukin-8 (IL-8) (Walters et al, 2005). Matrix metalloproteinases (MMPs), a family of zinc endo-peptidases, may also play an important role in COPD pathology (Babusyte et al, 2007; Haq et al, 2010). Particularly it has been described that MMP-1 is expressed in the lung of human patients with emphysema but not in normal control subjects (Imai et al, 2001).…”
Section: Introductionmentioning
confidence: 99%